Antimicrobial resistance trends in clinical Escherichia coli and Klebsiella pneumoniae in Ethiopia - Abera A. Kitaba; Zelalem T. Bonger; Degefu Beyene; Zeleke Ayenew; Estifanos Tsige; Tesfa Addis Kefale; Yonas Mekonnen; Dejenie S. Teklu; Elias Seyoum; Abebe A. Negeri (AOSIS, 2024)
Background: Clinicians rely on local antimicrobial resistance pattern data to guide empiric treatment for seriously ill patients when culture and antimicrobial susceptibility testing results are not immediately available. Objective: This study aimed to analyse 5-year trends in antimicrobial resistance profiles of Escherichia coli and Klebsiella pneumoniae isolates. Methods: Bacteriology reports from 2017 to 2021 at the Ethiopian Public Health Institute were analysed retrospectively. Isolates were identified using either the VITEK 2 Compact system, the BD Phoenix M50 instrument, or conventional biochemical tests. Antimicrobial susceptibility testing was conducted using either the Kirby-Bauer disk diffusion method or the VITEK 2 Compact system and BD Phoenix M50 systems available at the time of testing. The Cochran Armitage trend test was employed to test the significance of antimicrobial resistance trends over time. P-values less than 0.05 were considered statistically significant. Results: Of the 5382 bacteriology reports examined, 458 (9%) were on E. coli and 266 (5%) were on K. pneumoniae. Both K. pneumoniae (88%) and E. coli (65%) demonstrated high resistance to extended-spectrum cephalosporins. However, both K. pneumoniae (14%) and E. coli (5%) showed lower rates of resistance to carbapenems compared to other antimicrobials. In K. pneumoniae, resistance to carbapenems (from 0% to 38%; p 0.001) and ciprofloxacin (from 41% to 90%; p 0.001) increased significantly between 2017 and 2021. Conclusion: Both organisms showed very high resistance to broad-spectrum antibiotics. Additionally, K. pneumoniae demonstrated a statistically significant rise in ciprofloxacin and carbapenem resistance. What this study adds: This study emphasises the significance of regular reporting of local antimicrobial resistance patterns as this information can guide appropriate empiric therapy and efforts to address antimicrobial resistance issues.